GE_GERICHTE C/26946/2020 vom 19. September 2022 - GE Cour de justice (2022)
MAINLEVÉE DÉFINITIVE;SUSPENSION DE LA PROCÉDURE;COMPORTEMENT IRRESPECTUEUX;EXIGIBILITÉ;CRÉANCE | CPC.126; CPC.132; LLCA.12.letC; LP.80.al1; LP.81.al1